The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/en14238100
|View full text |Cite
|
Sign up to set email alerts
|

Introductory Review of Energy Efficiency in Buildings Retrofits

Abstract: Energy-efficient building retrofits must be approached from three perspectives: law regulation approach, financial incentives approach, and practice approach. The concepts of zero energy building and life cycle energy building are presented as the basis for energy retrofits. Multi-criteria boards to assess the decision-making process are reviewed, analysed, and categorised under an architectonic perspective. Some examples are presented, with different packages of measures, from deep to non-invasive energy retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Energy-efficient retrofits often have advanced technologies and features that can enhance performance and functionality. In [61], the authors used a multi-criteria decision analysis including location, climate, and operational and embodied energy, but not limited to architectural constraints, control, and management from a life cycle analysis perspective. They found that retrofitting the building envelope, lighting fixtures, and HVAC equipment can be an effective energy efficiency solution.…”
Section: Resultsmentioning
confidence: 99%
“…Energy-efficient retrofits often have advanced technologies and features that can enhance performance and functionality. In [61], the authors used a multi-criteria decision analysis including location, climate, and operational and embodied energy, but not limited to architectural constraints, control, and management from a life cycle analysis perspective. They found that retrofitting the building envelope, lighting fixtures, and HVAC equipment can be an effective energy efficiency solution.…”
Section: Resultsmentioning
confidence: 99%
“…Other technical approaches to energy-efficient building retrofits included law regulation, financial incentives, and practical considerations (performance-based architectural design) [84]. The current mandatory building energy regulations in certain regions (e.g., the hot summer-cold winter region of China) were deemed insufficient to achieve significantly lower carbon emissions, suggesting the need for more ambitious regulations [85].…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, we will review the use of AI technology in buildings to improve energy management and IEQ. Over the years, several reviews and studies have been carried out on improving energy management and IEQ in buildings using different methods [21][22][23][24][25]. Recent strides in technology have led to increasing interest in the use of AI, ML, and related technology to achieve better and more reliable results.…”
Section: Introductionmentioning
confidence: 99%